Kensington ou Tintin au pays des Runologues - Christophe Bord (Anglophonia)
The following pages present a survey of the century-old, fairly heated debate over the most famous runic forgery of all time known as the Kensington inscription, from the name of the place where it was found at the very end of the nineteenth century by a Swedish farmer in the “Scandinavian” state of Minnesota.Although crushing new evidence speaking against the authenticity of the monument surfaced a few years ago, a group of unwavering believers are still championing the cause of what they see as irrefutable proof of Scandinavian presence in the heart of the New World a century ahead of Columbus. We also suggest some of the (subconscious) causes of their “faith”.